Examining technical students’ feedback and perceptions on the use of Microsoft teams in asynchronous language learning - Rosnani, Ismail; Siti Norzaimalina, Abd Majid (UPM, 2024)
Student feedback is an invaluable tool for enhancing the teaching and learning process. It not only serves as a mechanism for students to engage with the course material but also provides instructors with insights for improving instructional design. Kutasi (2023) classified feedback as written, oral, online, and peer feedback, and the significance of formative assessment within the educational system lies in its ability to facilitate effective feedback between educators and students. Lim et al. (2020) found that personalised feedback helps students refine or strengthen important forethought processes of goal setting and reduce procrastination. Continuous communication between students and instructors promotes interactive learning environments, which will contribute to better learning outcomes.